2010
DOI: 10.2174/157016110793563889
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Infection in Carotid Plaque Pathogenesis and Stability: The Clinical Evidence

Abstract: There is considerable evidence supporting the contribution of other commonly encountered pathogens in the pathogenesis and rupture of the carotid plaque. Research in this direction should not be abandoned and further studies are necessary to elucidate the exact role of common infections in the pathogenesis and development of CPD and how this can be translated into novel pharmacological approaches for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…In the present study, the connection of procalcitonin level with the presence of unstable ICA stenoses was not confirmed, either. Determination of procalcitonin levels is a test used in clinical practice for diagnosing bacterial infections with a systemic response, which are included among the probable factors participating in the pathogenesis of atherosclerosis [6, 38]. However, the role of infections of atherosclerotic plaques in their destabilisation has not been unequivocally confirmed [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the connection of procalcitonin level with the presence of unstable ICA stenoses was not confirmed, either. Determination of procalcitonin levels is a test used in clinical practice for diagnosing bacterial infections with a systemic response, which are included among the probable factors participating in the pathogenesis of atherosclerosis [6, 38]. However, the role of infections of atherosclerotic plaques in their destabilisation has not been unequivocally confirmed [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…In‐depth studies on the aetiology, pathogenesis and clinical treatment of CHD have identified other important pathogenic factors in addition to the traditional risk factors of smoking, hypertension, diabetes and dyslipidaemia . Since the 1990s, researchers have provided evidence that infection is one of the risk factors for atherosclerosis and thrombus formation and that systemic inflammation due to infection promotes and accelerates the initiation and progression of atherosclerosis …”
Section: Introductionmentioning
confidence: 99%
“…Of these, H. pylori eradication has been reported to improve performance and increase lifespan in Alzheimer's disease patients [19], while two case reports indicated virtually complete recovery from long-term (3 years) misdiagnosed dementia/Alzheimer's disease following antifungal treatment for C. neoformans infection [20,21]. Many of these pathogens including herpes simplex, HHV-6, C. Pneumoniae, H. pylori and the periodontal pathogen, P. Gingivalis, have also been implicated in atherosclerosis [22][23][24][25], while C. neoformans infection in rabbits induces an increase in neutrophil superoxide production, plasma lipid peroxidation, and an increase in inflammatory cells, forerunners of atherosclerosis [26]. Atherosclerosis of the carotid arteries, or of the circle of Willis and leptomeningeal arteries, is a significant predictor of risk in dementia or Alzheimer's disease and correlates with Alzheimer's disease pathology [27,28].…”
Section: Introductionmentioning
confidence: 99%